Smoking Habits and Attitudes in Students of the Third Faculty of Medicine of Charles University in Prague - Schneidrová, Dagmar; Herotová, Tereza Kopřivová; Šustková, Magdaléna; Hynčica, Viktor (Central European journal of public health, 2016)
AIM: This study seeks to assess smoking habits, attitudes and intention to quit in students of the Third Faculty of Medicine of Charles University in Prague, Czech Republic. METHODS: A cross-sectional survey designed to obtain information on smoking history, current smoking status, cessation attempts, and attitudes towards smoking among health professionals was conducted in 452 students of the first and last years of a 6-year Master's Study Programme (General Medicine) and a 3-year Bachelor's Study Programme (Public Health). An anonymous questionnaire was administered during the classes in the course of academic years 2011-12 and 2012-13. RESULTS: 5.7% of the Master's Study Programme students (3.3% women and 9.0% men ) and 4.8% of the Bachelor's Study Programme students reported that they are regular smokers. The share of regular smokers was almost twice as big in students of the English Curriculum of the Master's Programme (10.7%) in comparison with the students of the Czech Curriculum (4.5%), and more than twice as big in students of the last years of both study programmes (3.9% in students of the 1st year and 10.8% in students of the 6th year of the Master's Programme; 3.2% in students of the 1st year and 7.0% in students of the 3rd year of the Bachelor's Study Programme). At the time of the research, 18.9% of students of the Master's Programme and 17.1% of students of the Bachelor's Programme were occasional smokers. 5.9% of students of the Master's Programme and 19.0% of students of the Bachelor's Programme reported that they quit smoking during their studies at the medical faculty; on the contrary, 9.8% of students of the Master's Programme and 14.3% of students of the Bachelor's Programme started smoking during that time. CONCLUSIONS: Smoking in health professionals undermines their significant role in health promotion and prevention of chronic diseases in their patients. Therefore, education at the medical faculty should focus on motivation of future health professionals towards non-smoking except providing knowledge on current research and guidance on early identification and further intervention in smokers.
Keywords: tobacco use; kouření; Cross-Sectional Studies; Česká republika; studenti lékařství; průzkumy a dotazníky; mužské pohlaví; smoking cessation; education; průřezové studie; Adult; Czech Republic; Smoking Cessation; health professions students; Smoking; ženské pohlaví; Humans; Surveys and Questionnaires; Students, Medical; Attitude to Health; postoj ke zdraví; dospělí; Female; odvykání kouření; lidé; Male